Respuesta :

Answer:

x = 25

Step-by-step explanation:

The mistake here is the squaring. When you square one side, you have to do the same on the other side:

[tex]\sqrt{3x+6}[/tex] = 9

[tex](\sqrt{3x+6}) ^{2}[/tex] = [tex]9^{2}[/tex]

3x + 6 = 81

3x = 75

x = 25

Ben

[tex]\huge\boxed{x=25}[/tex]

The mistake is in Step 1. The solver should have also squared [tex]9[/tex] when squaring the other side of the equation.

Correctly solving

[tex]\begin{aligned}\sqrt{3x+6}&=9\\(\sqrt{3x+6})^2&=9^2\\3x+6&=81\\3x+6-6&=81-6\\3x&=75\\\frac{3x}{3}&=\frac{75}{3}\\x&=25\end{aligned}[/tex]